THE INVESTIGATION OF CuOx ANODE INTERLAYER EFFECT IN WORKING PERFORMANCE AND CHARGE CARRIER TRANSPORT IN HYBRID SOLAR CELLS WITH INVERTED STRUCTURE - (NIM : 20210022); Pembimbing : Dr. Rachmat Hidayat, TULUS
The research was focused on hybrid solar cells with inverted structure, which constructed from bulk heterojunction using polymer blend of P3HT (donor) and PCBM (acceptor) as its active layer and CuOx (anode) thin film as anode interlayer. CuOx was used for replacing PEDOT:PSS that commonly used nowadays to serve as electron blocking or, in other words, as hole transport. The CuOx thin film is consisted of CuO and Cu2O, where the ratio seems to be dependent on the fabrication process. The valence band energy of Cu2O is about -5.2 eV, which is suitable as hole transport interlayer for P3HT based solar cells. The fabricated solar cells has ITO/AZO/P3HT:PCBM/CuOx/Ag structure, where the energy band of those layers produce an inverted structure of solar cell. AZO and CuOx thin layers were prepared by sol gel method, while P3HT:PCBM was prepared by spin coating method. Ag electrode was deposited by thermal evaporation method. The physical properties of CuOx thin films were firstly investigated in detail by UV-Vis, XPS, XRD, and AFM measurements. The solar cell performances were found to be affected by the physical properties and nanostructures of CuOx interlayer. Among the fabricated solar cells, by using the CuOx interlayer the experimental results show improvements in PCE: from 0.06% to 0.721%, EQE/IPCE at excitation wavelength of 500 nm: from 12.27% to 28.25%, and photocurrents generated at the absorption peak (2.54 eV): from 0.34 mA/cm2 to 0.76mA/cm2. In addition, it was also observed remarkable increase in its transient photocurrents spectrum in solar cells with CuOx layer.